2007
DOI: 10.1038/sj.leu.2404886
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between two fludarabine-based reduced-intensity conditioning regimens before allogeneic hematopoietic stem-cell transplantation: fludarabine/melphalan is associated with higher incidence of acute graft-versus-host disease and non-relapse mortality and lower incidence of relapse than fludarabine/busulfan

Abstract: Comparison between two fludarabine-based reduced-intensity conditioning regimens before allogeneic hematopoietic stem-cell transplantation: fludarabine/melphalan is associated with higher incidence of acute graft-versus-host disease and non-relapse mortality and lower incidence of relapse than fludarabine/busulfan A Shimoni, I Hardan, N Shem-Tov, A Rand, C Herscovici, R Yerushalmi and A NaglerThe Division of Hematology and Bone Marrow Transplantation, Chaim Sheba Medical Center, Tel-Hashomer, IsraelReduced-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
78
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 40 publications
11
78
2
Order By: Relevance
“…We have previously shown that acute GVHD rates are lower after BU-based RIC/RTC than MAC, and that severe mucositis, which is rare after FT, is also associated with high rates of acute GVHD. 3,24 Limiting tissue damage may decrease cytokine release and activation of the GVHD cascade. Pre-clinical models have also shown that treosulfan is associated with a favorable pattern of secretion of proinflammatory cytokines, including TNF-a, IFN-g, and in particular IL-2, that is less supportive of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that acute GVHD rates are lower after BU-based RIC/RTC than MAC, and that severe mucositis, which is rare after FT, is also associated with high rates of acute GVHD. 3,24 Limiting tissue damage may decrease cytokine release and activation of the GVHD cascade. Pre-clinical models have also shown that treosulfan is associated with a favorable pattern of secretion of proinflammatory cytokines, including TNF-a, IFN-g, and in particular IL-2, that is less supportive of acute GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects of dose intensity were seen in acute leukemia and in other hematologic malignancies, especially when the malignancy is not in a good remission. 30,31 However, there is an inherent bias in studies with this methodology related to the difference in patient characteristics between patients allocated to myeloablative conditioning and RIC.…”
Section: Discussionmentioning
confidence: 99%
“…Chemosensitivity at the time of SCT is one of the most important factors in allogeneic SCT for all hematologic malignancies including myeloma. 30,31 Similarly, the EBMT study demonstrated that patients with progressive disease do not benefit from allogeneic SCT with RIC. 15 The GVM effect may not be potent enough to overcome bulky or highly resistant disease.…”
Section: Discussionmentioning
confidence: 99%
“…HSCT performed with various preconditioning regimens has been attempted to rescue these patients, and some positive effects have been obtained. [4][5][6][7][8][9] HSCT using myeloablative preconditioning regimens resulted in an increased frequency of TRM, [4][5][6] and therefore HSCT with nonmyeloablative preconditioning regimens has also been tried. However, early relapse and remission induction failure were often observed in such patients.…”
Section: Introductionmentioning
confidence: 99%